Multihop-Based Optimal Cluster Heads Numbers Considering Relay Node in Transmission Range of Sensor Nodes in Wireless Sensor Networks. (16th May 2013) - Nam, Choon-Sung; Bae, Sang-Tae; Chung, Jin-Wook; Shin, Dong-Ryeol
Abstract : The data transmission of sensor nodes which detect events might be affected by their neighbor nodes located in their communication range. Thus, we analyze the energy consumption of sensor networks as a function of the number of cluster heads considering the above two options, multihop-based communication and the case where a neighbor node is in the transmission range for communicating data. This helps us to elect the number of energy-efficient cluster heads in a more practical manner. Also, we determine the effect of electing the number of cluster heads by restricting the local cluster size.